NOVEL APPROACHES FOR ANEMIA IN CARDIORENAL SYNDROME: A RANDOMIZED CONTROLLED TRIAL OF HYPOXIA-INDUCIBLE FACTOR PROLYL HYDROXYLASE INHIBITOR VS SGLT2 INHIBITOR - LAXMI SANKALPA BHAGANAGARAPU; SARUMATHY SUNDARARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study was designed to compare and discern the effects of desidustat versus dapagliflozin in managing anemia in addition to the standard treatment in cardiorenal syndrome (CRS). Methods: Patients were randomly allocated into three groups: Group A (standard heart failure therapy+oral hypoglycemics), Group B (standard therapy+dapagliflozin), and Group C (standard therapy+desidustat). At baseline, 12 weeks, and 24 weeks, the hematology, iron-related parameters were estimated. The Kidney Disease Quality of Life questionnaire (KDQOL-36) was used to evaluate the quality of life of these patients. Results: After 24 weeks, Group C exhibited significant improvements with a rise in hemoglobin (Hb) (p=0.001), other hematology, and iron parameters. Group B showed a modest but significant increase in Hb (p=0.04) alongside improved glycemic parameters. In contrast, KDQOL scores improved in Group C, specifically for the burden of kidney disease (p=0.03), symptoms (p=0.001), and daily life impact (p=0.001). Group B also showed significant changes in the burden of kidney disease (p=0.04), symptoms (p=0.002), and daily life impact (p=0.001). In Group A, significant changes were observed in the burden of kidney disease (p=0.001) and the impact on daily life (p=0.01). Conclusion: Desidustat demonstrated greater hematopoietic efficacy compared to dapagliflozin and standard therapy alone, hence emerging as a better treatment choice over conventional treatment in managing anemia in CRS.